Vibration Characteristic Analysis of Spur Gear System with Coupled Damage - Li Xike Wang Jian Chen Tao Zhang Jun (Jixie chuandong)
As a conventional form of gear failure，crack-wear coupled damage dramatically changes the vibration characteristics of a gear transmission system .In order to verify the influences of the coupled damage on the vibration characteristics of the transmission system，a dynamics model of spur gear transmission system，in which included the effect of crack and wear，is established，and its vibration analysis is carried out. Firstly，the nonlinear dynamics model of spur gear transmission system is established by means of lumped parameter method，the influence of tooth crack on mesh stiffness of gear pair is analyzed based on potential energy method. The comprehensive quantity of tooth surface wear is calculated by wear simulation，and the tooth surface wear is being introduced to the displacement excitation of the transmission system. Then，the steady dynamics responses of the transmission system are solved by Runge-Kutta method，and the vibration characteristics of spur gear system with crack-wear coupled damage mode are analyzed. The results show that crack-wear coupled damage induce amplitude modulation and frequency modulation of the system vibration，and it will produce more obvious mesh impact than a single damage.